2018
DOI: 10.1002/nur.21873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms in older nursing home residents with intact cognitive function in Taiwan

Abstract: The investigators aimed to explore the prevalence of depressive symptoms and associated factors among older residents with intact cognitive function in nursing homes in Taiwan. A cross-sectional descriptive and correlational research design was used. A convenience sample of 178 older residents without cognitive impairment was recruited from 36 nursing homes in Southern Taiwan. The questionnaires included demographic data; the Barthel Index, which assesses the ability to perform activities of daily living; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Our cohort study design allowed an assessment of HR, providing more information than OR about subsequent risk of depression. We also found that lower income, living alone, and substance abuse were significant risk factors of depression, which were compatible with previous studies [ 26 29 ]. The possible explanation is the lack of financial or emotional support may predispose people to depression.…”
Section: Discussionsupporting
confidence: 93%
“…Our cohort study design allowed an assessment of HR, providing more information than OR about subsequent risk of depression. We also found that lower income, living alone, and substance abuse were significant risk factors of depression, which were compatible with previous studies [ 26 29 ]. The possible explanation is the lack of financial or emotional support may predispose people to depression.…”
Section: Discussionsupporting
confidence: 93%
“…2 Department of Psychiatry, Chang Gung Memorial Hospital at Linkou, Tao-Yuan, Republic of China. 3 College of Nursing, Chang Gung University of Science and Technology, Chia-Yi, Republic of China. 4 Research Fellow, Chang Gung Memorial Hospital at Chiayi, Chai-Yi, Republic of China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Placement of older adults in a nursing home (NH) can be a stressful life event that produces a higher prevalence of depression [1][2][3], loneliness, and a reduction in quality of life (QoL) [4,5]. Depression is a leading cause of disability worldwide and feelings of loneliness contribute significantly to depression, resulting in reductions in QoL [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the prevalence of depression in nursing homes is twice that of older people living at home. However, older people living on their own are often insufficiently diagnosed (Chow et al, 2004; Drageset et al, 2011; Hu et al, 2018; Kramer et al, 2009). In a field study, Kramer et al showed that around 30% of nursing-home residents suffer from acute depression, whereas only 42.9% of patients with major depression were diagnosed as such.…”
Section: Social Isolationmentioning
confidence: 99%